Economic reforms in Sri Lanka, post-1977 period - Sarvananthan, Muttukrishna; International Centre for Ethnic Studies (Colombo : International Centre for Ethnic Studies, 2005)
On economic policies in various government sectors, post 1977 and the political changes during the period; contributed articles presented earlier at a workshop in July 2002 at ICES.
"ICES Sri Lanka program"--Cover.
Keywords: Sri Lanka -- Economic policy -- Congresses; Sri Lanka -- Politics and government -- 1978- -- Congresses